2014
DOI: 10.1680/geot.14.t.012
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of MgO–GGBS and CS–GGBS stabilised marine soft clays to sodium sulfate attack

et al.

Abstract: Reactive magnesia (MgO) and carbide slag (CS) were used to activate ground granulated blastfurnace slag (GGBS) to stabilise a marine soft clay, and the stabilised clays were subjected to accelerated sodium sulfate attack. The results indicated MgO-GGBS stabilised clay was nearly inert to this sodium sulfate solution. The resistance of CS-GGBS stabilised clay to sodium sulfate attack was lower than that of MgO-GGBS stabilised clay, but higher than that of Portland cement stabilised clay. Unlike CS-GGBS stabilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…3) Less calcium ions in the MSB system also means the formation of expansive gypsum and ettringite can be effectively limited, which has been proved in (Yi et al 2014) where only C-S-H, Ht and a small amount of ettringite were observed in MgO-GGBS paste exposed to Na2SO4 solution. Excessive formation of ettringite can produce high expansive force to crack the matrix leading to spalling and higher hydraulic conductivity (Cai et al 2014;Neville 2004).…”
Section: Discussionmentioning
confidence: 96%
“…3) Less calcium ions in the MSB system also means the formation of expansive gypsum and ettringite can be effectively limited, which has been proved in (Yi et al 2014) where only C-S-H, Ht and a small amount of ettringite were observed in MgO-GGBS paste exposed to Na2SO4 solution. Excessive formation of ettringite can produce high expansive force to crack the matrix leading to spalling and higher hydraulic conductivity (Cai et al 2014;Neville 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Through a mercury intrusion porosimetry (MIP) test, Yi et al (2014a) quantified that the total pore volume of a 90-day MgO-GGBS-stabilised clay was 10% lower than that of the corresponding Ca(OH) 2 -GGBS-stabilised clay.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Under those low temperatures, the MgO has high surface area, high reactivity, and low crystallinity (Shand, 2006). The use of reactive MgO with GGBS for soil stabilisation is a recent development offering a range of mechanical and durable advantages over PC or lime-slag blends (Jegandan et al, 2010;Yi et al, 2014bYi et al, , 2014cYi et al, , 2012. Yi et al (2014c) found that MgO-GGBS blend in the ratio of 1:9 by weight induced a higher unconfined compressive strength of stabilised sand and clayey silt than lime-GGBS blend at the same ratio at 7 days, although they obtained a similar strength range at 90 days.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the soil treated by GGBS-MgO mixture with proper ratio may achieve a strength ~1.3-4 times higher than the corresponding PC treated soil. Jegandan et al (2010) and Yi. et al (2014b) found that the combination of MgO and GGBS in stabilisation produced higher resistance to sulfate and acid attack than PC stabilised soil, since no expansive phase ettringite formed in MgO-GGBS stabilised soil.…”
Section: Introductionmentioning
confidence: 99%